College writing skills - Langan, John (McGraw-Hill, 2005)
This text is intended for composition courses designed to help students master the five-paragraph essay. It focuses on four essential bases of effective writing - unity, support, coherence and sentence skills. A wide variety of activities and assignments are provided, both structured and creative.